Always REDy efficient and effective Philippine Red Cross facilities - Domingo, Sarakiel Ysabel P.; Sicam, Olivia Alma G. (Quezon City College of Architecture, University of the Philippines Diliman, 2022)
Emergency medical services (EMS) are an important part of a country's health care system. In the Philippines, the largest provider of EMS is a non-governmental humanitarian organization-- the Philippine Red Cross (PRC). The infrastructure and facilities of the PRC can be improved to meet the current needs of the community.
The current headquarters of the PRC in Mandaluyong is of utmost importance in EMS provision in the Philippines. It serves as an ambulance depot, a command center, a blood center, and a training center. It was not designed for maximum efficiency for the regular operation of EMS since it is a repurposed office building. In addition, the establishment of more national outposts is key to the successful operations of the PRC all over the country. These outposts and the new information infrastructure they provide for the organization should be considered in the spatial planning of the headquarters.
This paper addresses the aforementioned issues through the application of more humane and interactive architecture principles in its design. A design for informational outposts adapted to the typhoon-ridden climate and made easier to construct is developed to be reproduced at different sites in the country to provide better informational infrastructure. The development of outposts would hasten the information gathering and transfer and make decision-making and response faster in times of emergencies. Through this project, an efficient and effective PRC headquarters can be designed and guidelines for future EMS facilities can be explored and developed. This project can help make better use of the limited resources of the underserved EMS so that it can reach more people and save more lives.
includes appendices.
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Philippine Red Cross; Emergency medical services -- Philippines